PENGARUH KARAKTER DAN COLLATERAL NASABAH TERHADAP KREDIT DI BMT MUHAMMADIYAH CILACAP - Rahman, Yasir Abdul (JURNAL EKONOMI, 2017)
The problem discussed in this research is how the influence of character and collateralinfluences the smoothness of credit at BMT Muhammadiyah Cilacap. The sample of thisstudy is 100 people. The research method with quantitative descriptive statisticalapproach with the type of explanatory research. The results showed that characters andcollateral significantly influence the smoothness of credit, while the characters havedominant influence over collateral.Keywords: Character, Collateral